On a Maximum Principle and Uniqueness Theorems for a System of First Order Equations of Mixed Type (Journal of Partial Differential Equations, 1996)
A maximum principle for a system of first order equations of mixed type is established. The uniqueness theorems of solutions t.o the generalized Tricomi type problem and to the Frankl's problem are proved by the method of auxiliary functions.